2020
DOI: 10.1371/journal.pone.0238389
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of language representation and the influence of epilepsy surgery on language reorganization in children and young adults with focal lesional epilepsy

Abstract: Mapping brain functions is crucial for neurosurgical planning in patients with drug-resistant seizures. However, presurgical language mapping using either functional or structural networks can be challenging, especially in children. In fact, most of the evidence on this topic derives from cross-sectional or retrospective studies in adults submitted to anterior temporal lobectomy. In this prospective study, we used fMRI and DTI to explore patterns of language representation, their predictors and impact on cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…We also performed an analysis in a subpopulation in which preschool children were excluded. Young children have an increase likelihood of epilepsy‐driven relocalization of language regions, may display a bilateral distribution of language areas prior to surgery, and can exhibit a greater postoperative functional recovery, 53 , 55 , 106 all of which may predispose to a lower rate of transient and/or permanent dysphasia. This low risk of language deficit was corroborated by our study in which only one preschool child (1/31) exhibited a transient dysphasia and none were permanently disabled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also performed an analysis in a subpopulation in which preschool children were excluded. Young children have an increase likelihood of epilepsy‐driven relocalization of language regions, may display a bilateral distribution of language areas prior to surgery, and can exhibit a greater postoperative functional recovery, 53 , 55 , 106 all of which may predispose to a lower rate of transient and/or permanent dysphasia. This low risk of language deficit was corroborated by our study in which only one preschool child (1/31) exhibited a transient dysphasia and none were permanently disabled.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of auras (e. pain or laryngeal constriction during seizure), side of hemispheric dominance, and postoperative dysphasia were reported both for the entire cohort and excluding preschool age children (<6 years) as this subgroup is inherently different and is generally unable to report subjective manifestations, 32 , 50 , 51 has higher likelihood of atypical language representation (eg, right‐side or bilateral), and harbors neuroplasticity with greater potential for postoperative language recovery, respectively. 52 , 53 , 54 , 55 …”
Section: Methodsmentioning
confidence: 99%
“…SDE, however, offers a high density of contacts on the cortical surface (gyral crowns), which can be helpful when mapping eloquent cortex, particularly when atypical functional representation is suspected. 23,24 SEEG is the preferred method of intracranial investigation of deep structures or lesions and a suspected bottom of sulcus dysplasia. Overall, SDEs and SEEG are fundamentally unique procedures and have comparable outcomes.…”
Section: Subdural Grids Versus Seeg In Pediatric Epilepsymentioning
confidence: 99%
“…More recently, HLD has been investigated using microstructural DTI properties, such as fractional anisotropy (FA), in the context of the presurgical evaluation of epilepsy and tumours (Tantillo et al, 2016; Barba et al, 2020). Some studies have reported relationships between language lateralisation and interhemispheric asymmetry of diffusion characteristics or the size of the corpus callosum (Tantillo et al, 2016), while others did not (Barba et al, 2020). A fundamental issue in presurgical patient studies is the increased prevalence of functional and structural reorganisation of language networks and abnormal language lateralisation (Yogarajah et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several structural MRI and diffusion tensor imaging (DTI) studies have examined the relationship between HLD and white matter volume and have reported that leftward language lateralisation is associated with a greater volume of the arcuate fasciculus (Propper et al, 2010) and the number of tracts in the corpus callosum (Timocin et al, 2020). More recently, HLD has been investigated using microstructural DTI properties, such as fractional anisotropy (FA), in the context of the presurgical evaluation of epilepsy and tumours (Tantillo et al, 2016; Barba et al, 2020). Some studies have reported relationships between language lateralisation and interhemispheric asymmetry of diffusion characteristics or the size of the corpus callosum (Tantillo et al, 2016), while others did not (Barba et al, 2020).…”
Section: Introductionmentioning
confidence: 99%